Introduction to and Discussion Summary of William Tay's Colonialism, Cold War Era, and Marginal Space: The existential Conditions of Four Decades of Hong Kong Literature - Birus, Hendrik (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
In the context of the Second International Conference on Humanistic Discourse, this text introduces William Tay's "Colonialism, the Cold War Era, and Marginal Space: The Existential Conditions of Four Decades of Hong Kong Literature" and reports on the central concerns that emerged in its discussion.